Kesiapan Dosen dalam Menghadapi Perubahan - Nashiruddin, Muhammad Faishal; Nur’Aini, Siti; Wibowo, Danan Satriyo (Jurnal Psikologi, 2024)
Lecturers in facing new challenges in carrying out the tridharma of higher education continue to increase along with developments over time. So, lecturers' readiness to change needs to be considered. The changes currently experienced by lecturers are in reporting lecturer workload (BKD) using SISTER and changes in the management of functional positions. This research aims to determine the picture of lecturers' readiness for change (readiness for change) within the Muhammadiyah University of Jember environment. The subjects in this research involved lecturers at Muhammadiyah University of Jember who had a minimum functional position of expert assistant (AA). The sampling technique used in this research uses probability sampling using stratified random sampling. Sample calculations in this study used the Slovin formula and there were 150 samples in this study. Data analysis in this study used simple linear regression. The results of this research show that lecturers' readiness for change is high on average (around 50.55% of the total sample) which indicates that lecturers are ready to face changes that occur in lecturer workload reporting (BKD) using SISTER and changes in position management functional.